Large mixed-frequency VARs with a parsimonious time-varying parameter structure - Thomas B. Götz; Klemens Hauzenberger (Deutsche Bundesbank, 2018)
To simultaneously consider mixed-frequency time series, their joint dynamics, and possible structural changes, we introduce a time-varying parameter mixed-frequency VAR. To keep our approach from becoming too complex, we implement time variation parsimoniously: only the intercepts and a common factor in the error variances vary over time. We can therefore estimate moderately large systems in a reasonable amount of time, which makes our modifications appealing for practical use. For eleven U.S. variables, we examine the performance of our model and compare the results to the time-constant MF-VAR of Schorfheide and Song (2015). Our results demonstrate the feasibility and usefulness of our method.
Keywords: C32; C51; C53; 330; Mixed Frequencies; Time-Varying Intercepts; Common Stochastic Volatility; Bayesian VAR; Forecasting